1998
DOI: 10.1177/174182679800500201
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Central Obesity and Age-Specific Waist: Hip Ratio of People in Five Cities: The Indian Women's Health Study

Abstract: Objective To study the prevalence of central obesity and agespecific waist: hip ratio of urban women from five Indian cities.Design and setting Cross-sectional surveys were conducted in 6-1 2 urban streets in different parts of India using similar methods of sample selection and criteria of diagnosis. Subjects and methodsWe randomly selected 321 2 women, aged 25-64 years, from Moradabad (n =902), Trivandrum (n = 760), Calcutta (n =365), Nagpur (n = 405), and Bombay (n=780). Evaluation was by a questionnaire ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Studies conducted in Sub-Saharan Africa have reported an increase in the prevalence of obesity among both men and women in urban areas (6,7). Other epidemiological surveys in developing countries have shown that an unhealthy diet contributes to the increasing problem of obesity (8,9). Similarly, there has been a significant variability in the levels of dyslipi demia in the urban areas of Sub-Saharan Africa (10), and a possible increase in rural areas has also been sug gested (11).…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in Sub-Saharan Africa have reported an increase in the prevalence of obesity among both men and women in urban areas (6,7). Other epidemiological surveys in developing countries have shown that an unhealthy diet contributes to the increasing problem of obesity (8,9). Similarly, there has been a significant variability in the levels of dyslipi demia in the urban areas of Sub-Saharan Africa (10), and a possible increase in rural areas has also been sug gested (11).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, measuring the abdominal adiposity ratio is considered as the reference method for studying overweight and obesity. Anthropometric measurements such as body mass index (BMI) or waist and hip circumference are generally the most commonly used indicators to assess overweight or obesity (Mushtaq et al, 2011;Singh et al, 1998). However, these markers should be considered as a rough guide because they may not correspond to the same degree of fatness in different individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent publications from India (Shelgikar et al, 1991;Ramachandran et al, 1992;Gupta and Majumdar, 1994;Gupta and Mehrishi, 1997;Singh et al, 1998aSingh et al, , 1998bGhosh et al, 2000;Bose and Das Chaudhuri, 2001;Bhadra et al, 2002) have reported the significant association of abdominal or central adiposity with established risk factors for CHD in various ethnic groups. A more recent study by Dasgupta and Hazra (1999) had recommended that a WC cut-off point of 80 cm could be used to define centrally obese individuals among Bengalee men.…”
Section: Introductionmentioning
confidence: 99%